Students' Learning Difficulties And Their Relationship With Biology Learning Outcomes Of Class XI Students at SMA N 8 Padang During Online Learning - Sinaga, Chairunnisa; Gusmaweti, Gusmaweti; Azrita, Azrita; Deswati, Lisa (International Journal of Education and Teaching Zone, 2022)
his research is motivated by students who have difficulty in the online learning process is the low learning outcomes obtained from students. This study aims to analyze what factors influence the biology learning difficulties of students in class XI IPA at SMA Negeri 8 Padang during online learning and to determine the relationship between students' learning difficulties in biology through online learning and student biology learning outcomes. This research is descriptive research. The population of this research is class XI IPA which consists of 3 classes totaling 110 students. The research sample amounted to 33 students. The sampling technique is a random sampling technique with a sample proportion of 30%. The research data were analyzed using descriptive analysis and then a t-test to determine the correlation. The results showed that the highest score of the student learning difficulty factor was 2.81, namely the motivation and interest in student learning factors, and the lowest difficulty factor obtained a score of 2.44, namely social interaction. There is a relationship between students' learning difficulties in biology through online learning with biology learning outcomes with a value of r = 0.520; the coefficient of tcount value of 4.642 is greater than ttable of 2.040, so it can be concluded that there is a positive and significant relationship between learning difficulties in biology through online learning and student learning outcomes and there are suggestions for schools to be positive inputs in efforts to build and improve models. online/online learning and is also able to improve student learning and it is hoped that teachers and parents can recognize and observe online learning difficulties experienced by these students.